The first data on bat ectoparasites (Acarina, Insecta) in the Baikal region and Yakutia (eastern Siberia) - Orlova, Maria; Kazakov, Denis; Zakhahrov, Evgeny; Troeva, Irina; Vladimirov, Leonid (Check List, 2016)
This paper summarizes new data on ectoparasites from bats (Chiroptera: Vespertilionidae) from eastern Siberia (Russia). The existence of 14 bat ectoparasite species is confirmed for this territory, including eight species of gamasid mites (Gamasina: Spinturnicidae, Macronyssidae) and six species of insects belonging to two orders (Insecta: Diptera, Siphonaptera). The bedbugs (Insecta: Heteroptera: Cimicidae) found are undefined. These findings include six species (one species of gamasid mites and five species of insects) not previously reported from eastern Siberia. New hosts are described for some ectoparasites.